OhioLINK – recent developments at a United States academic library consortium. Issue 4 (21st November 2016) - Evans, Gwen; Schwing, Theda
Abstract : Purpose: This paper aims to provide an update to Tom Sanville's 2007 overview of OhioLINK, a renowned US academic library consortium, and describe the current state of activity and services. Design/methodology/approach: The approach used is descriptive. Findings: OhioLINK's main collaborative services include document delivery, resource sharing and the establishment of digital libraries, including electronic journals, electronic books and open-access materials such as electronic theses and dissertations. This update to Tom Sanville's 2007 overview of OhioLINK issues and developments describes the current state of collaborative library services and resource sharing a decade later, including the challenges of hosted institutional repositories and the implications of shifting from shared print to e-book collections at the network level. Originality/value: OhioLINK trends provide a snapshot of changing activity and sustainability in library resource sharing at network scale across many different types of academic libraries.